How Do Design Students Design Visual Identity & Packaging Design For Innovative Food Products? Results From Four Batches of Design Studio Class - Hananto, Brian Alvin (de-lite, 2025)
Visual identity and packaging design are essential parts of a product, especially food products. To teach students of the Universitas Pelita Harapan’s Visual Communication Design Department about packaging design, the author collaborated with Universitas Pelita Harapan’s Food Technology Department to design their innovative food products. After four years of classroom action research, the author attempts to review and evaluate the literature and designs of the 2016-2019 cohort to understand how the students had been designing a visual identity and packaging design. The result of the study is that the students had been drawing inspiration from the product, product’s ingredient, product’s benefit, taste, and sensation, presented image, and culture. The inspirations are then implemented as graphic elements, illustrations, character designs, and typography. The result of this study is a framework that the author hopes can be implemented in the next class’s cohort.